Evaluasi Pelaksanaan Program Pelatihan Pembelajaran Mendalam (PM) bagi Guru SMPN 2 Praya Tengah Menggunakan Model Countenance Evaluation Stake - Nurul Hidayati; Abdul Kadir Jaelani (Mataram University, 2026)
This study aims to evaluate the implementation of the Deep Learning (Pembelajaran Mendalam/PM) training program for teachers at SMPN 2 Praya Tengah using the Stake evaluation model, which consists of antecedents, transactions, and outcomes. The study employed a qualitative approach, with data collected through interviews, observations, and documentation. The research subjects included five teachers participating in the training, the school principal, and the training instructor. The findings indicate that in the antecedents aspect, the Deep Learning training was conducted based on teachers’ real needs to improve the quality of more meaningful and student-centered learning. Institutional support was generally adequate, although limitations were found in facilities and funding. In the transactions aspect, the training process was participatory and collaborative, utilizing various methods such as discussions, simulations, and hands-on practice that encouraged active teacher engagement, despite challenges related to time management and depth of material coverage. In the outcomes aspect, the training had a positive impact on improving teachers’ understanding, self-confidence, and skills in designing and implementing deep learning in the classroom; however, implementation still faced constraints related to limited time and students’ readiness. Based on these results, it can be concluded that the Deep Learning (PM) training for teachers at SMPN 2 Praya Tengah is effective and relevant to school needs, yet it requires continuous support and follow-up mentoring to ensure its impact contributes optimally to improving the quality of learning.